2017
DOI: 10.1371/journal.pone.0189456
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on fatty acid metabolism in skeletal muscle mitochondria of untrained and endurance-trained rats

Abstract: We studied the effects of various assay temperatures, representing hypothermia (25°C), normothermia (35°C), and hyperthermia (42°C), on the oxidation of lipid-derived fuels in rat skeletal muscle mitochondria of untrained and endurance-trained rats. Adult 4-month-old male Wistar rats were assigned to a training group (rats trained on a treadmill for 8 weeks) or a sedentary control group. In skeletal muscle mitochondria of both control and trained rats, an increase in the assay temperature from 25°C to 42°C was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
3
19
0
Order By: Relevance
“…The elevated PGC-1α in the MGS has been observed also after 4 and 8 weeks of training ( Fig 9 ). This result is in agreement with our previous study showing that 8 weeks of endurance training up-regulates mitochondrial biogenesis markers such as Nrf2, PGC-1α as well as proteins involved in fatty acid metabolism [ 68 ]. On the other hand, an increase in mtDNA copy number was found at the final stage of training (8 weeks) in both the MGF and MGS ( Fig 7 ).…”
Section: Discussionsupporting
confidence: 93%
“…The elevated PGC-1α in the MGS has been observed also after 4 and 8 weeks of training ( Fig 9 ). This result is in agreement with our previous study showing that 8 weeks of endurance training up-regulates mitochondrial biogenesis markers such as Nrf2, PGC-1α as well as proteins involved in fatty acid metabolism [ 68 ]. On the other hand, an increase in mtDNA copy number was found at the final stage of training (8 weeks) in both the MGF and MGS ( Fig 7 ).…”
Section: Discussionsupporting
confidence: 93%
“…It is well established that the maximal rate of muscle fatty acid oxidation is higher during physical exercise. Physical resistance training induces expression of the fatty acid transporter cluster of differentiation 36 (CD36) in muscles [12,13]. Studies with pharmacological and immunologic CD-36 inhibitors have shown that the antiangiogenic signaling mediated by CD36 and thrombospondin 1 (TSP-1) is dependent on protein tyrosine kinases Fyn and Lyn, and Src kinases [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, miRNA-mRNA network analysis of circBBS9 annotated top genes in metabolic pathways from KEGG analysis as its potential target genes, which supported a possible regulatory role of circBBS9 in the metabolic programs in myocytes. For example, LDHA, AMD1, DNMT3A and ACADSB were reported to regulate muscle cell proliferation and muscle atrophy [28][29][30][31], while ACADS, CS, GATM, CHSY1 were related to muscle energy metabolism [32][33][34]. Thus, aging and aerobic training, two opposite processes impact muscle functionality, may exert their impacts by modulating the circBBS9-miRNA-mRNA network.…”
Section: Discussionmentioning
confidence: 99%